ATTAPULGITE CLAY OF THE VENTZIA BASIN, WESTERN MACEDONIA, GREECE, AS TEMPLATE IN SYNTHESIZING AMORPHOUS CARBON NANOTUBES - Koukakis, P.; Tsakiridis, P.; Ntziouni, A.; Kordatos, K.; Perraki, M. (Bulletin of the Geological Society of Greece, 2016)
Attapulgite from the Ventzia Basin, Western Macedonia, Greece, was used as a template for preparing amorphous carbon nanotubes by vapor deposition polymerization (VDP) method and two different alcohols, furfuryl alcohol and ethylene glycol, as carbon source. The morphology and structure of the as prepared carbon nanotubes were investigated by means of scanning electron microscopy and a transmission electron microscopy. X-ray diffraction and Raman spectroscopy were additionally employed. The amorphous nature of the carbon nanotubes has been confirmed by the XRD and the SAED pattern, as well as the Raman spectrum. No noticeable difference was observed in the morphology and structure of the as prepared carbon nanotubes regarding the type of alcohol used as carbon source. However, a difference in the quantity of the produced carbon nanotubes was noticed, with the furfuryl alcohol, as carbon source, producing a larger amount of carbon nanotubes than the ethylene glycol.